Polypharmacy in older adults with cancer undergoing radiotherapy: A review. Issue 6 (July 2022) - Novak, Jennifer; Goldberg, Annette; Dharmarajan, Kavita; Amini, Arya; Maggiore, Ronald J.; Presley, Carolyn J.; Nightingale, Ginah
Abstract: Polypharmacy is characterized by the simultaneous use of multiple medications, including prescription drugs, over-the-counter drugs, and nutritional supplements. Polypharmacy is known to increase the risk of adverse drugs reactions, drug-drug interactions, and medication errors, and to negatively impact quality of life. The prevalence of polypharmacy varies by population, but has been reported to exceed 90% among older adults with cancer. Polypharmacy may be exacerbated among older adults with cancer receiving radiation therapy due to the resulting acute or chronic side effects that need to be managed with additional medications. The medications prescribed to manage radiation-related side effects increase the risk of adverse drug events, as do changes in nutritional status related to the secondary side effects of radiation treatment. Side effects from treatment may result in the need for breaks in cancer therapy or treatment delays, which ultimately can lead to worse oncologic outcomes. Few studies have examined polypharmacy in the context of older adults undergoing radiation therapy. We sought to review the literature pertaining to polypharmacy among older adults with cancer and discuss implications specifically for those individuals undergoing radiation therapy. This paper presents a narrative review of studies published in the past decade that provided detailed information on polypharmacy in older adults undergoing radiation therapy for cancer. The review elucidated good practices to avoid adverse drug events from polypharmacy, but more studies are warranted to develop standard guidelines.